Penyelesaian Perkara Perceraian Melalui Mediasi Sebagai Upaya Perdamaian (Studi Putusan No: 0317/Pdt.G/2014/PA.Tnk) - Meita Djohan OE (Universitas Bandar Lampung (UBL), 2017)
One of the things the completion of the process of a divorce through mediation as peace efforts between the Plaintiff against the Defendant. The problem in this research is how the divorce settlement through mediation as peace efforts in case No. 0317 / Pdt.G / 2014 / PA.Tnk ?. The approach used in this research is normative juridical approach and empirical approach. Data was collected by library research and field studies. Qualitative data analysis. Divorce settlement through mediation as peace efforts in Decision No. 0317 / Pdt.G / 2014 / PA.Tnk conducted by the Religious Court Judge Mediator by the pre mediation, the mediation process level, then mediation reached an agreement formulated in writing and signed by the parties and the mediator. Suggestions in this research is a mediator should continue to improve professionalism by continuing to hone the potential to participate in various education and training to adapt to the development of mediation techniques.